Polygeneration-Annex: Combining lignite-based power generation and syngas-based chemicals production. (1st September 2017) - Gootz, Matthias; Forman, Clemens; Wolfersdorf, Christian; Meyer, Bernd
Abstract: Due to the high share of renewable power in Germany, existing base-load lignite-fired power plants suffer from low capacity utilization. In combination with a Coal-to-Liquids (CTL) facility, the power generation utilization might increase. Such combined polygeneration concepts, called 'Annex', have been developed at TU Bergakademie Freiberg. Consisting of a small-capacity gasifier (in comparison to boiler size) and a subsequent synthesis unit, the Annex plant exports steam and fuel gases to the linked power plant. Moreover, the Annex serves as a power sink for this power plant. Capital expenditure can be reduced through the usage of existing coal delivery and pretreatment facilities. Using the commercial software packages Aspen Plus and Ebsilon Professional, a techno-economic study is conducted to investigate synergies for novel Annex concepts. Both entrained-flow and fluidzed-bed gasification are analyzed for a 200 MW(th) gasifier, equivalent to 60, 000–70, 000 t/a of synthesis products. The current study is investigating the linking of Methanol-to-Gasoline, Methanol-to-Olefins and Fischer-Tropsch Annex concepts to a 600 MW(el) power plant fired with Rhenish lignite. Concerning the thermal power plant, no significant efficiency losses are observed and coal consumption is reduced compared to stand-alone solutions. Based on the capacity estimation method, investment costs are analyzed and can be reduced by up to 17.7% for the Annex CTL. In the future, this polygeneration concept could also be applied to newly constructed power plants.